Marker-assisted selection and genomic selection - Unêda-Trevisoli, Sandra Helena [UNESP]; da Silva, Fabiana Mota [UNESP]; Mauro, Antonio Orlando Di [UNESP] (Springer Nature, 2017)
Breeding techniques and molecular tools, i.e., biotechnology, have increased crop yield over the last century. Marker-assisted selection and, more recently, genome-wide association studies and genomic selection have been used as tools of breeding programs, especially in the resistant genotype selection. The genomic association study refers to significant associations between a loci and an interesting trait. Genomic selection is based on the effects of single nucleotide polymorphism (SNP) markers distributed throughout the genome, where the number of markers must be sufficiently high so all quantitative trait loci are in linkage disequilibrium with at least one marker. Thousands of markers distributed throughout the genome at reduced costs, as well as the easy access to biotechnologies, are the main way of aggregating these techniques in breeding programs. Several studies have shown that genomic selection is highly effective for improving crop yield. This tool increases the genetic gain of improved populations by increasing selection accuracy and, mainly, by reducing the generation intervals.
Keywords: Genome-wide association study; Glycine max; SNP